The effectiveness evaluation of interdepartmental cooperation in the long-term care services provision for elderly and disabled citizens - S. E. Titor (Вестник университета)
The effective provision of social services for long-term care of elderly citizens and the disabled requires the interaction of many structures, including the nongovernmental sector. The organization of interdepartmental interaction contributes to the work efficiency of these structures. The study analyzes the experience of interdepartmental interaction in the provision of long-term care for the elderly and disabled, the paper shows the best regional practices of such interaction. For the purposes of the study, an array of regional legislation on the care of the elderly and disabled, including interdepartmental interaction, was analyzed. The study revealed that there are original models of such interaction in the regions. The analysis results made it possible to formulate proposals for improving legislation on the regulation of interdepartmental interaction. This positive experience can be translated both for use in other regions and at the federal level.